2007
DOI: 10.1086/517497
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Atazanavir-Based Highly Active Antiretroviral Therapy in Patients with Virologic Suppression Switched from a Stable, Boosted or Unboosted Protease Inhibitor Treatment Regimen: The SWAN Study (AI424-097) 48-Week Results

Abstract: In patients with virologic suppression who were receiving other PIs, switching to a once-per-day regimen containing atazanavir provided better maintenance of virologic suppression (as demonstrated by significantly lower rates of virologic rebound and treatment failure than those observed with continued unmodified therapy), a comparable safety profile, and improved lipid parameters, compared with those for patients who continued their prior PI-based regimen through 48 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 12 publications
5
98
0
Order By: Relevance
“…Altogether, over 264 extendedly discontinuous treatment years, HIV escaped control in 18 instances, amounting to 7 escapes per 100 highly discontinuous treatment years, within the range of viral escapes noted in a number of 7 days per week combinations (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), yet lower than on unremitting PI monotherapy (45)(46)(47)(48). Congruent with the tentative exploratory nature of our prescriptions, 14 of the 18 escapes could reasonably be linked to unfitting prescriptions or EA (Table 3).…”
Section: Iccarre 4 Day Per Week Treatment: Not a Single Hiv Escapementioning
confidence: 67%
See 1 more Smart Citation
“…Altogether, over 264 extendedly discontinuous treatment years, HIV escaped control in 18 instances, amounting to 7 escapes per 100 highly discontinuous treatment years, within the range of viral escapes noted in a number of 7 days per week combinations (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), yet lower than on unremitting PI monotherapy (45)(46)(47)(48). Congruent with the tentative exploratory nature of our prescriptions, 14 of the 18 escapes could reasonably be linked to unfitting prescriptions or EA (Table 3).…”
Section: Iccarre 4 Day Per Week Treatment: Not a Single Hiv Escapementioning
confidence: 67%
“…Yet, not just any medicinal treatment simplification will do; the alleviation of triplecombination therapy with 2 drugs as maintenance therapy, 7 days per week, once failed radically (65)(66)(67)(68), and ritonavirboosted PI monotherapies, 7 days per week, have yet to match (45-48) current triple combination standards virologically (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Treatment Outcomes Following Viral Escapesmentioning
confidence: 99%
“…8,16,18 Another notable benefit of ATV may be the potential adherence advantage because ATV/r administration is once daily rather than the twice daily for IDV/r. 38 Moreover, due to its higher genetic barrier to ARV mutations, ATV/r is one of the PIs recommended by the US Department of Health and Human Services (DHHS) and International AIDS Society as a possible first-line choice (GuidelineREF).…”
Section: Visits (In Months)mentioning
confidence: 99%
“…46 Patients (n = 419) were randomized 2:1 to switch to ATV (400 mg od) or, if they were receiving TFV, to ATV/r (300/100 mg od), or to continue to receive their existing PI. They concluded that in patients with virological suppression who were receiving …”
Section: Patient-focused Perspectivesmentioning
confidence: 99%